Deep Reinforcement Learning for Scan Recognition and Path Planning of Rescue UAVs - Ma, Minchao (International Journal of Computer Science and Information Technology, 2024)
In recent years, rapid advances in communication and navigation technologies have led to the research of drones in disaster relief becoming a controversial topic of interest. These drones are capable of autonomously performing high-risk tasks under extreme and treacherous conditions, such as searching and locating disaster victims, effectively replacing human intervention. The purpose of this essay is to discuss the basic overview of rescue UAVs, to find how deep reinforcement learning techniques on the MATLAB platform can be used to improve the effectiveness of UAV recognition scanning and path planning. Subsequently discuss the future development path and potential applications of rescue UAV technology in a forward-looking manner.